Legge sulla cittadinanza, la residenza e l’accesso N. CXXXI – legislative reorganisation of the sitizenship of Vatican City-State - Witola, Filip (The Opole Studies in Administration and Law, 2024)
The citizenship of the Vatican City State is characterised by individual features relating above all to the manner in which it is conferred and its forfeiture. The introduction of the legal category of Vatican nationality has its origins in the Lateran Treaty, but it was in 1929 when Pope Pius XI promulgated the law Legge sulla cittadinanza ed il soggiorno N. III concretising this institution which has lived to see its own reorganisation over time. Based on an analysis of Vatican legislation, it is possible to conclude that the present Vatican legislation is largely updated to current needs without losing its unique characteristics. The main intention was to present whether and how Legge sulla cittadinanza, la residenza e l’accesso N.CXXXI changes Vatican citizenship and what differences can be found in the newly created law. This process was based on a comparative method of legal acts, an analysis of the literature, as well as observation of interrelationships and dependencies. On the basis of this exercise, it was determined that the 2011 law remains within the original legal framework, but that its amendment is of a practical nature, intended to give individuals freedom of action and not to lead them to the appearance of possible negative consequences associated with the loss of citizenship.